(untitled) (Itinera, 2023)
Divina Commedia represents Dante’s most famous work: even if many centuries have passed, it still represents universal knowledge. Today comics are still perceived as consumer literature, however over time there have been many comics works that have reinterpreted in various ways Commedia. Various reinterpretations have been conducted using interwined and different languages. Reinterpretations accompany Dante’s world in today’s world. The issue entitled Dante and comics contains essays that investigate the links between Commedia and comics through two perspectives: philosophical, linguistic and literary. The authors develop a number of central subjects: comics as a transmedia medium based on drawn from reflections on aesthetics and the artistic improvisation practices; the role that comics can take as a medium to bring students closer to language and literature; the type of language found in the comics and an accurate analysis of the language itself; the results of classroom activities that start from texts taken from Commedia; an in-depth study about various visual Commedia translations that have followed one another over the centuries. From the reflections it emerges versatility and liveliness offered by the transposition of Commedia into comics, allowing the texts to be examined on several levels of interpretation in which the possibilities arising from topics are recognized and broadened. Contributions have a philosophical, linguistic and literary impact.